LAW ENFORCEMENT REGARDING VIOLATIONS OF REGIONAL RESTAURANT TAXES IN LABUHANBATU UTARA DISTRICT IS REVIEWED FROM REGIONAL REGULATION NUMBER 9 OF 2011 CONCERNING RESTAURANT TAX - Heru Suhendro; Yasmirah Mandasari Saragih; Ismaidar (CV. RADJA PUBLIKA, 2024)
Restaurant Tax is a tax on services provided by restaurants for a fee, which also includes restaurants, cafeterias, canteens, stalls, bars, and the like including catering/catering services, which are regulated in North Labuhanbatu Regency Regional Regulation Number 9 of 2011 concerning Local tax. This Empirical Legal Research focuses on how is law enforcement regarding restaurant tax violations in the North Labuhanbatu District in terms of Regional Regulation Number 9 of 2011? And what are the inhibiting factors in collecting restaurant tax in North Labuhanbatu Regency? The data source used is primary data, obtained from field research and documents, and supplemented with secondary data. The results of the research conducted show that law enforcement regarding restaurant tax violations in North Labuhanbatu Regency based on North Labuhanbatu Regency Regional Regulation Number 9 of 2011 concerning Regional Taxes is still very lacking, especially criminal law enforcement in accordance with the provisions contained in this regulation.